Aktivitas pemasaran melalui media sosial instagram dan ekuitas merek serta pengaruhnya terhadap niat beli konsumen - Bimo Satrio Djati; Agus Abdurrahman (CV. Kurnia Grup, 2024)
The purpose of this research is to determine the influence of Social Media Marketing Activities on brand equity; to determine the influence of brand equity on E-WOM; to determine the influence of E-WOM on consumer purchasing intentions and to determine the influence of Social Media Marketing Activities on consumer purchasing intentions. Research data collection was carried out using a cross sectional approach carried out over a 1 month period using questionnaires distributed via social media. Researchers distributed questionnaires to consumers who made online purchases to students in Yogyakarta. The analysis tool uses SEM AMOS. The research results show that there is a significant relationship between social media marketing activities and brand equity; there is a significant relationship between brand equity and e-wom; There is no influence of the e-WOM variable on purchase intention and there is a significant relationship between social media marketing activities and purchase intention.